Amplifying Proficiency: Unearthing the Impact of Extensive Listening on Student Listening Skills - Rani Aryanti Rukmana; Sri Setyarini; Pupung Purnawarman; Isra F Sianipar (Universitas Hamzanwadi, 2023)
In conventional language education, listening often receives less attention compared to the teaching of grammar and other language skills. Nevertheless, it is crucial to acknowledge that knowledge acquisition and assimilation primarily occur through listening. This study explores the enhancement of students' listening competency through extensive listening practices, utilizing the participatory action research method, specifically the Collaborative Classroom Action Research approach. The research was conducted at Junior High School in Medan, Indonesia and involved 31 Grade VIII students. The study incorporated pre-test and post-test listening assessments, and observation across three cycles: pre-cycle, cycle I, and cycle II. The results clearly demonstrate the positive impact of extensive listening on students' listening skills. Overall, there was a substantial improvement, with scores increasing from 49.35% in the pre-test to an impressive 85.16% in cycle II. Notably, individual progress also showed substantial growth, rising from 6.45% in the pre-test to a remarkable 77.4% in cycle II. These findings underscore the undeniable effectiveness of extensive listening in language education. They offer valuable insights for English teachers and provide robust support for the adoption of extensive listening as a potent means to nurture and elevate students' listening skills, which are a fundamental aspect of language acquisition.